Edwardsiella piscicida infection reshapes the intestinal microbiome and metabolome of big-belly seahorses: mechanistic insights of synergistic actions of virulence factors - Zhang, Lele; Wang, Fang; Jia, Longwu; Yan, Hansheng; Gao, Longkun; Tian, Yanan; Su, Xiaolei; Zhang, Xu; Lv, Chunhui; Ma, Zhenhao; Xue, Yuanyuan; Lin, Qiang; et al. (Frontiers in Immunology, 2023)
Uncovering the mechanism underlying the pathogenesis of Edwardsiella piscicida-induced enteritis is essential for global aquaculture. In the present study, we identified E. piscicida as a lethal pathogen of the big-belly seahorse (Hippocampus abdominalis) and revealed its pathogenic pattern and characteristics by updating our established bacterial enteritis model and evaluation system. Conjoint analysis of metagenomic and metabolomic data showed that 15 core virulence factors could mutually coordinate the remodeling of intestinal microorganisms and host metabolism and induce enteritis in the big-belly seahorse. Specifically, the Flagella, Type IV pili, and Lap could significantly increase the activities of the representative functional pathways of both flagella assembly and bacterial chemotaxis in the intestinal microbiota (P < 0.01) to promote pathogen motility, adherence, and invasion. Legiobactin, IraAB, and Hpt could increase ABC transporter activity (P < 0.01) to compete for host nutrition and promote self-replication. Capsule1, HP-NAP, and FarAB could help the pathogen to avoid phagocytosis. Upon entering epithelial cells and phagocytes, Bsa T3SS and Dot/Icm could significantly increase bacterial secretion system activity (P < 0.01) to promote the intracellular survival and replication of the pathogen and the subsequent invasion of the neighboring tissues. Finally, LPS3 could significantly increase lipopolysaccharide biosynthesis (P < 0.01) to release toxins and kill the host. Throughout the pathogenic process, BopD, PhoP, and BfmRS significantly activated the two-component system (P < 0.01) to coordinate with other VFs to promote deep invasion. In addition, the levels of seven key metabolic biomarkers, Taurine, L-Proline, Uridine, L-Glutamate, Glutathione, Xanthosine, and L-Malic acid, significantly decreased (P < 0.01), and they can be used for characterizing E. piscicida infection. Overall, the present study systematically revealed how a combination of virulence factors mediate E. piscicida-induced enteritis in fish for the first time, providing a theoretical reference for preventing and controlling this disease in the aquaculture of seahorses and other fishes.